IMPLEMENTASI SEGETIGA RESTITUSI DALAM MENINGKATKAN DISIPLIN POSITIF PESERTA DIDIK DI SMP NEGERI 2 KOTA PAGAR ALAM - Yunita, Tiara; Alfarabi, Toriq (Algebra : Jurnal Pendidikan, Sosial dan Sains, 2025)
This study aims to explore the implementation of the restitution triangle in promoting positive discipline among ninth-grade students in Islamic Religious Education at state junior high school 2 Kota Pagar Alam, and to identify both the supporting and inhibiting factors faced by teachers in applying this approach. The research uses a qualitative method with a descriptive analytical approach. Data was collected through observation, interviews, and documentation. The findings show that the restitution triangle has been implemented at state junior high school 2 Kota Pagar Alam by Islamic Religious Education teachers and has led to noticeable changes in students’ attitudes and behavior. Supporting factors include adequate teaching facilities such as the use of projectors, and the presence of proactive teachers. Inhibiting factors include the diversity among students, low self-awareness, peer influence, external environmental factors brought into the school, and the role of parents.